1997
DOI: 10.1074/jbc.272.7.4276
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized Activation of the High Affinity Immunoglobulin E Receptor within Membrane Domains

Abstract: The earliest known step in the activation of the high affinity IgE receptor, Fc⑀RI, is the tyrosine phosphorylation of its ␤ and ␥ subunits by the Src family tyrosine kinase, Lyn. We report here that aggregation-dependent association of Fc⑀RI with specialized regions of the plasma membrane precedes its tyrosine phosphorylation and appears necessary for this event. Tyrosine phosphorylation of ␤ and ␥ occurs in intact cells only for Fc⑀RI that associate with these detergent-resistant membrane domains, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
344
2
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(385 citation statements)
references
References 46 publications
38
344
2
1
Order By: Relevance
“…Such high-density complexes were also observed in cells solubilized with 0.5% Triton X-100, i.e. after treatment that prevented the association of aggregated Fc 4 RI with DRM (not shown), suggesting that they represent complexes of Fc 4 RI with the cytoskeleton [5,10]. Pretreatment of the IgE-sensitized cells for 40 min with 10 mM methyl-g -cyclodextrin (MBCD) before adding anti-IgE Ab or anti-Fc 4 RI mAb P Fig.…”
Section: Differences In Degranulation Calcium Response and Drm Recrumentioning
confidence: 86%
See 2 more Smart Citations
“…Such high-density complexes were also observed in cells solubilized with 0.5% Triton X-100, i.e. after treatment that prevented the association of aggregated Fc 4 RI with DRM (not shown), suggesting that they represent complexes of Fc 4 RI with the cytoskeleton [5,10]. Pretreatment of the IgE-sensitized cells for 40 min with 10 mM methyl-g -cyclodextrin (MBCD) before adding anti-IgE Ab or anti-Fc 4 RI mAb P Fig.…”
Section: Differences In Degranulation Calcium Response and Drm Recrumentioning
confidence: 86%
“…To test how the extent of aggregation of Fc 4 RI correlates with association of the receptors with DRM, cells were exposed to 125 I-labeled 5.14 or H10 mAb for 5 min and solubilized in ice-cold 0.06% Triton X-100; this solubilization procedure preserves the association of aggregated Fc 4 RI with DRM [5,6]. In control cells exposed to 125 I-IgE instead of anti-Fc 4 RI Ab, most of the 125 I-IgEFc 4 RI complexes (94±8%; mean ± SD, n=4) were found in the high-density fractions of the sucrose gradient (fractions [11][12][13][14][15][16][17][18][19][20][21][22], and only a small portion (5.8±2.2%) was found in the low-density fractions (fractions 1-10; Fig.…”
Section: Differences In Degranulation Calcium Response and Drm Recrumentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies with detergent-solubilized cells implied that FceRI-mediated activation is initiated by coalescence of aggregated FceRI with DRM [10,12] and that F-actin is involved in this process [19,20]. However, EM observations failed to discern any significant increase in association between Thy-1 and aggregated FceRI [12,15].…”
Section: Cross-talk Between Thy-1 and Fcerimentioning
confidence: 99%
“…Biochemical studies of isolated detergent-resistant membranes (DRM) showed that they are rich not only in GPI-anchored proteins, but also in palmitoylated Src family protein tyrosine kinases [6,7] and palmitoylated transmembrane adaptor proteins, including linker for activation of T cells (LAT) [8] and non-T cell activation linker (NTAL) [9]. Importantly, in nonactivated mast cells, the FceRI is excluded from DRM, whereas in FceRI-activated cells most of the receptor is associated with DRM in a cholesterol-dependent manner [10][11][12]. These findings suggested that FceRI-mediated activation is initiated through association of the aggregated FceRI with membrane microdomains possessing signal transduction machinery.…”
Section: Introductionmentioning
confidence: 99%